1986
DOI: 10.1111/j.1365-2990.1986.tb00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Stringhalt in Horses: A Distal Axonopathy

Abstract: A detailed investigation of the neuropathology of a horse affected with stringhalt was performed. Qualitative and quantitative light and electron microscopy, and single teased fibre preparations of peripheral nerve demonstrated predominantly axonal degeneration, the stage of which was appropriate for the duration of clinical signs. There was selective involvement of large myelinated nerve fibres. A proximal to distal increase in the severity of pathological changes was present in the peripheral nerves. The lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 16 publications
(10 reference statements)
4
36
1
Order By: Relevance
“…The 2nd form, Australian or acquired bilateral stringhalt, is a manifestation of distal axonopathy. 7,8 Large myelinated fibers are selectively affected with a decrease in severity distal to proximal.…”
Section: Treatment and Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…The 2nd form, Australian or acquired bilateral stringhalt, is a manifestation of distal axonopathy. 7,8 Large myelinated fibers are selectively affected with a decrease in severity distal to proximal.…”
Section: Treatment and Outcomementioning
confidence: 99%
“…8,15 The most severely affected nerves included the recurrent laryngeal and superficial and deep peroneal nerves, which showed mixed axonal degeneration and demyelination with concurrent atrophy of the innervated muscles. No alterations in the central nervous system have been found.…”
Section: Treatment and Outcomementioning
confidence: 99%
“…4,6,23,39 Disorders affecting the peripheral nerves resulting in denervation atrophy of muscle also occur. 8,13,14,34,41 Most survey studies of equine neuromuscular disease are of clinical cases. 9,17 A slaughterhouse study of equine muscle reported only on the incidence of intramuscular protozoa.…”
Section: Introductionmentioning
confidence: 99%
“…Different hypotheses have been proposed to explain the hyperflexion observed in AS (Cahill et al, 1986;Cahill and Goulden, 1992;Slocombe et al, 1992). Stringhalt is currently thought to be associated with damage to the axons (axonopathy) in the peripheral long nerves (Cahill and Goulden, 1992;Armengou et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of AS is still unknown, outbreaks of this disease have been associated to grazing pastures where Hypochaeris radicata predominates and other plants such as Taraxacum officinale and Malva parviflora may be present (Huntington et al, 1989;Cahill and Goulden, 1992). There have been reports of outbreaks of AS in New Zealand, Australia, USA, Chile, Brazil, France, and probably Japan (Cahill et al, 1986;Huntington et al, 1989;Cahill and Goulden, 1992;Slocombe et al, 1992;Gay et al, 1993;Dixon et al, 2001;Takahashi et al, 2002;Domange et al, 2010). The AS has not been reported in Colombia before.…”
Section: Introductionmentioning
confidence: 96%